RETORIKA IMAJI FILANTROPI ISLAM MODERN DALAM PRANGKO AMAL MUHAMMADIYAH - Adib Sofia (Jurnal Sosiologi Agama, 2021)
In pre-independence era until several decades after, stamps become very precious things either functionally or conceptually. At that time stamps functioned not only as the proof of payment for sending letters or documents but also as the fundraising tool or usually called charity stamps. Muhammadiyah charity stamps issued in Dutch East Indies period have become the modern Islamic philanthropic icons. Until their 80 years of existence in 2021, these stamps are still being discussed and performed in various media. Therefore, this writing is trying to reveal the meaning of stamps in several stages and in various contexts. First, in terms of denotative image, it can find the detailed description of visual and textual form of the charity stamps. Second, in terms of connotative rhetoric, it can find the meaning of stamps as (i) the confession of Dutch East Indies Government to Islamic movement; (ii) the professionalism of Islamic philanthropy; (iii) humanitarian actions from general public for general public; and (iv) a form of spirituality and social worship. Third, on the mystical stage it can find the meaning of (i) collective culture of sustainability to manage the philanthropy in organized manner and (ii) collective culture of sustainability to live religion happily. These three of meanings have answered why the existence of Muhammadiyah charity stamps is still being appreciated until today.